2011
DOI: 10.4236/wja.2011.14029
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Fertility Desires among HIV Positive Women Living in the Western Highlands Province of Papua New Guinea

Abstract: The objective of this study was to identify determinants of fertility desires in HIV positive women living in the Western Highlands Province, Papua New Guinea, a male-dominated, patrimonial society. A cross-sectional study was conducted to collect data in February, 2010. Two hundred and ninety one HIV-infected women participated in personal interviews using a structured questionnaire. Sixty-six percent of the respondents were in polygamous relationships. Thirty-four percent of the participants desired a child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
19
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 20 publications
7
19
2
Order By: Relevance
“…Categorization was carried out based on the obtained total score by adding up three of the above-mentioned variables. The classification was made as lower (0-10), middle (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and upper (26-29). About threequarters of the participants were in the lower socio-economic class in the Socioeconomic Status Scale of Kuppuswamy (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Categorization was carried out based on the obtained total score by adding up three of the above-mentioned variables. The classification was made as lower (0-10), middle (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and upper (26-29). About threequarters of the participants were in the lower socio-economic class in the Socioeconomic Status Scale of Kuppuswamy (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…14 Similarly, a study in Papua New Guinea revealed that having no children in the family (AOR: 3.6, 95% CI: 1.5-8.9) was associated with fertility desire in PLHIV. 15 Having a CD4 cell count >500 cells/mm 3 was associated with fertility desire in a study conducted among HIV-infected people starting ART in Uganda. This may be due to the improvement in their health status increasing the commitment of these people to achieve their reproductive desires.…”
Section: Discussionmentioning
confidence: 98%
“…Rather, fertility desire was strongly associated with being young or childless, which both were likely to be interlinked one with the other and this kind of reflection is probably the reflection of the majority of human being in the fertile age regardless of HIV infection. In another study not included in this meta-analysis, being young or having few or no child was also an independent predictor for high fertility desire [16]. To the contrary, in another study, being young or single was reported to be inversely associated with fertility desire [39].…”
Section: Discussionmentioning
confidence: 99%
“…A partner’s desire for a child was one of the strongest predictors for women’s fertility desire [16]. In another study, being younger age, having fewer living children and higher quality of life were individually associated with fertility desire [17].…”
Section: Introductionmentioning
confidence: 99%
“…Persons infected with HIV are right-bearers. In line with this reasoning, two separate studies involving ARVexposed HIV-positive women in their reproductive ages found that a good number of them were sexually active, and desirous of having children (Aska, Chompikul, & Keiwkarnka, 2011;Loutfy et al, 2009). Some of the women (HIV-positive women living in Ontario, Canada), according to Loutfy et al had taken certain steps such as seeing a doctor and not using any contraceptive in order to conceive.…”
Section: Introductionmentioning
confidence: 85%